Profiling innovators in Kota Kinabalu: a study of self concept and impulse buying behaviour - Lo, Chang Chin (2007)
This study aims to establish the profiles of the innovators in Kota Kinabalu from two perspectives, self-concept and buying impulsiveness. A mall intercept survey was conducted in April 2007 in the various shopping centres located in urban Kota Kinabalu. A total of 158 questionnaires were collected for this study. The analytical plan involves using independent t-tests, bivariate correlation, multiple regression and hierarchical regression. This study found that the self concepts of innovators and non-innovators are indeed different. In particular, innovators tend to think of themselves as delicate, unpleasant, unorganized and irrational. This study also found that consumer innovativeness does have a significant influence on buying innovativeness and that innovators tend to be impulsive buyers. In examining the moderating effect of the demographic factors on the relationship between consumer innovativeness and self concepts, this study found that age is a significant moderator for only a pair of self concept adjective pairs, i.e. pleasant-unpleasant, amongst the 15 pairs used. On the other hand, gender and age are found to have significant moderating effect over the relationship between consumer innovativeness and buying impulsiveness.